Effects of Human Antithrombin III on Mortality and Blood Coagulation Induced in Rabbits by Endotoxin - Triantaphyllopoulos, D C (Thrombosis and Haemostasis, 1984)
Twenty-one rabbits were infused with 20μg/kg/hr of E. coli endotoxin for 6 hr. Eight of the animals were preinjected immediately before the infusion of endotoxin, with a bolus dose of human AT III calculated to increase the antithrombin content of the plasma by about 4 units/ml. All eight animals which were preinjected with AT III survived, while 5 of the 13 control rabbits infused with endotoxin alone died. The changes in coagulation parameters from the baseline values, between the 8 control rabbits which survived and the 8 animals which were preinjected with AT III were compared. The concentration of the preinjected human AT III declined significantly faster (P: <0.01) than that of the native rabbit AT III. AT III prevented the decline of F.XII throughout the infusion of the endotoxin. However, the decline in F.V, fibrinogen, prothrombin and platelets was not affected (P: >0.5) by the injection of AT III.
Keywords: Antithrombin III; Endotoxin; Intravascular coagulation